Nutritional Intake, Physical Activity and Quality of Life in COPD Patients - Chambaneau, A.; Filaire, M.; Jubert, L.; Bremond, M.; Filaire, E. (International Journal of Sports Medicine, 2016)
In this study, we aimed to document the level of physical activity (PA), quality of life, depression status and nutritional data of 20 individuals with chronic obstructive pulmonary disease (COPD) (mean age 65.0±7.0 years) admitted in hospital for pulmonary rehabilitation and compare these data to those obtained in 20 similarly aged healthy individuals. Nutritional data were collected using a 3-day diet record. COPD patients engaged in significantly less PA than healthy individuals and achieved a significant higher score of Beck Depression Inventory (BDI) than the control group. Their Fat Free Mass Index (FFMI) was significantly lower when compared to the control group (p<0.05). Patients had significantly lower total caloric intake, Vitamins B6, B9, B12, Vitamin E, β carotene and omega 3 than controls. Moreover, patients with low FFMI reported significantly lower mean intake of energy, carbohydrate, vitamin E and vitamin B6 than patients with normal FFMI. Because oxidative stress and inflammation are features of many lung diseases, nutrients with anti-oxidant and anti-inflammatory properties could be useful in prevention or treatment. Further work is needed to explore the possible relationship between the intake of B group vitamins, Vitamin E, n-3PUFAS and the development and progression of lung disease.
Keywords: COPD; dietary intake; quality of life; physical activity